A influência do sombreamento sobre diferentes atributos da comunidade de algas perifíticas. - Santos, Helivania Sardinha dos (2018)
Light is an essential component in the process of synthesis of the organic compounds by photosynthetic organisms. We tried to evaluate the influence of this variable on different attributes of the periphythic algae, important producers in the trophic webs of aquatic environments, through an experiment in mesocosmos with different levels of luminosity. In approach 1 we evaluated different levels of shading in the production of biomass of periphytic algae. The biomass was measured using the chlorophyll-a method. The highest biomass was found in the control treatment, not suffering from photoinhibition, while the lowest biomass was found in the treatment with 80% shading. In approach 2 we evaluated the influence of the high level of shading on the process of succession of periphytic algae through the variation of community density over time and between treatments. The community presented changes in its density between the beginning and end of the experiment, in addition to a change in its composition, with the class Bacillariophyceae being the most abundant at the beginning of the process of succession in a high level of shading and in the control treatment (without shading). This remained more abundant in the shade treatment and was replaced by Zygnemaphyceae in the control treatment. The adaptation of these algae due to the mainly photosynthetic pigments and accessories that they present in their constitution, are essential in the process of colonization and succession in the environments. We conclude that light is a variable of extreme importance, exerting direct influence on several attributes of the periphytic community.